Democratizing the Enemy : the Japanese American Internment. - Hayashi, Brian Masaru (Princeton University Press, 2010)
During World War II some 120,000 Japanese Americans were forcibly removed from their homes and detained in concentration camps in several states. These Japanese Americans lost millions of dollars in property and were forced to live in so-called "assembly centers" surrounded by barbed wire fences and armed sentries. In this insightful and groundbreaking work, Brian Hayashi reevaluates the three-year ordeal of interred Japanese Americans. Using previously undiscovered documents, he examines the forces behind the U.S. government's decision to establish internment camps. His conclusion: the motive.